EFFECT OF AGE ON SEMINAL CHARACTERISTICS OF JERSEY BULL SEMEN - BHATT, P; TIWARI, R P; JAISWAL, V K (The Indian Journal of Animal Reproduction, 2016)
Sixty ejaculates each from young (2.5-3 yr, n=5) and old (6-8 yr, n=5) Jersey bulls were evaluated for fresh and post thaw semen characteristics. The old bulls had higher (p<0.05) ejaculate volume, spermatozoa per ejaculate and abnormal spermatozoa. Various post thaw semen parameters viz. motility, live/abnormal spermatozoa, intact acrosome and HOST were similar (p>0.05) between young and old bulls. In brief, age has no predominant impact on seminal characteristics of Jersey bull semen